Analisis Kejahatan Terhadap Nyawa: Studi Kasus Penyerangan dan Pembunuhan di Green Lake City oleh John Kei - Ciek Julyati Hisyam; Anggie Natasya Putri; Aninda Rahma Melani; Anissa Nurul Chotimah; Jemima Fathima Pasha; Muhammad Sufyan Rabbani; Syifa Rahma Nabila (LPPM Politeknik Pratama, 2023)
Crimes against individuals and their lives have become frequent occurrences in Indonesia. These issues often arise from trivial matters or the current economic pressures. Some of these cases have become quite prominent and widely discussed in society. One of them is the case of an attack and murder that took place in Green Lake City, Tangerang City in 2020 by the criminal group led by Jhon Kei. This research aims to analyze the chronology of the attack and murder carried out by John Kei's criminal group through the lens of Sutherland's differential association theory. The focus of this study is to examine how each premise in the theory applies to this case. The research employs a Literature Review method as the primary approach. Data is collected through a review of literature, scientific articles, research reports, and official documents related to the attack and murder case in Green Lake City by John Kei. Data analysis is conducted by considering each premise in the differential association theory that is applicable to the case. The research findings will provide an analysis of the differential association theory in understanding the attack and murder case in Green Lake City by John Kei. This research is expected to offer insights into the case of the attack and murder that occurred in Green Lake City from the perspective of differential association theory.